2016
DOI: 10.1007/s10876-016-0986-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism in Simple Metal and 4d Transition Metal Clusters

Abstract: In this review article I discuss two aspects of magnetism in small metal clusters. The first question discussed is whether simple metal clusters, that obey electronic shell models and mimic properties of elemental atoms, also obey Hund's rule of maximum spin multiplicity. The second question is whether small clusters of 4d transition metal atoms, that are non-magnetic in the bulk, have magnetic ground states. The question arises because calculations showed that small V clusters are magnetic although the bulk m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Recently, a density functional theory (DFT) study reported a magnetic feature for the Na 55 and K 55 nanoclusters, which was suggested as a preponderant property in the enhancement of the thermal stability of icosahedral Na 55 + nanoclusters . On the other side, for Cs 55 , the geometric packing plays a dominant role in the stability of the icosahedron structure, which is explained by atomic characteristics, such as smaller size of the Cs atoms, relativistic effects, and sd hybridization. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a density functional theory (DFT) study reported a magnetic feature for the Na 55 and K 55 nanoclusters, which was suggested as a preponderant property in the enhancement of the thermal stability of icosahedral Na 55 + nanoclusters . On the other side, for Cs 55 , the geometric packing plays a dominant role in the stability of the icosahedron structure, which is explained by atomic characteristics, such as smaller size of the Cs atoms, relativistic effects, and sd hybridization. …”
Section: Introductionmentioning
confidence: 99%
“…Hund rule's relevance has long exceeded the boundaries of atomic physics where it was first formulated, over the years being investigated in many other systems such as quantum dots [6][7][8][9][10][11][12][13][14][15][16][17], artificial molecules created by quantum dots [18][19][20][21], metal clusters [23][24][25][26], bipartite lattices [27,28], ultrathin films [29] new carbon systems [30,31] or even in optical lattices [32,33].…”
Section: Introductionmentioning
confidence: 99%